Hierarchically porous CoNiO2 nanosheet array films with superior sodium storage performance. (7th November 2017) - Chang, Ling; Wang, Kai; Huang, Liangai; He, Zhishun; Shao, Haibo; Wang, Jianming
Abstract : The hierarchically porous CoNiO2 nanosheet array film prepared via a low-temperature solvothermal method manifests superior sodium storage performance. Abstract : Nanostructured transition metal oxides are considered as some of the promising anode materials for rapidly emerging sodium ion batteries. Herein, a hierarchically porous CoNiO2 nanosheet array film is prepared via a low-temperature solvothermal method with subsequent annealing treatment. As a self-supported anode for sodium ion batteries (SIBs), the as-prepared hierarchically porous CoNiO2 nanosheet array film manifests superior sodium storage performance. The film electrode delivers a large reversible capacity of 746.6 mA h g −1 after 100 cycles at 200 mA g −1 . In particular, a capacity of 419 mA h g −1 is achieved at a high current density of 1600 mA g −1, demonstrating a good rate capability.